MASYARAKAT DAN BUDAYA JAWA PESISIR UTARA - Mudjahirin Thohir (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
This paper focuses on qualitatively interpretive studies of the North Coast Javanese people and their culture. The underlying assumption is that in many ways, the people and culture of north coast Java are different from those of Inland Java. The results of the study showed that: (a) the north coastal Javanese community, is more dominated by the Islamic way than the general pattern of inland Javanese; (b) The choice of employment is more about being a trader than being a government employee; (c) In the merchant community, the social interaction model tends to be straightforward, and the level of Javanese Language used tends to be rough.